2014
DOI: 10.1021/jf500647h
|View full text |Cite
|
Sign up to set email alerts
|

Natural and Natural-like Phenolic Inhibitors of Type B Trichothecenein VitroProduction by the Wheat (Triticumsp.) PathogenFusarium culmorum

Abstract: Fusarium culmorum, a fungal pathogen of small grain cereals, produces 4-deoxynivalenol and its acetylated derivatives that may cause toxicoses on humans or animals consuming contaminated food or feed. Natural and natural-like compounds belonging to phenol and hydroxylated biphenyl structural classes were tested in vitro to determine their activity on vegetative growth and trichothecene biosynthesis by F. culmorum. Most of the compounds tested at 1.5 or 1.0 mM reduced 3acetyl-4-deoxynivalenol production by over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
102
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(108 citation statements)
references
References 46 publications
4
102
0
2
Order By: Relevance
“…Previous similar approaches, aimed at other synthases, were successfully validated [65,66]. Thus, we can reasonably expect that the chemicals proposed here would lead to a success story like the one we recently published [38].…”
Section: Discussionsupporting
confidence: 58%
“…Previous similar approaches, aimed at other synthases, were successfully validated [65,66]. Thus, we can reasonably expect that the chemicals proposed here would lead to a success story like the one we recently published [38].…”
Section: Discussionsupporting
confidence: 58%
“…On the one hand, a higher β-glucan content might enhance the resistance against DON accumulation thus contributing to type V resistance by antioxidant activity of β-glucan (Kofuji et al 2012). Indeed, several studies demonstrated the inhibitive potential of natural antioxidant compounds on the production of mycotoxins (Boutigny et al 2010;Pani et al 2014;Zhou et al 2007). On the other hand, a lower β-glucan content may allow the accumulation of DON.…”
Section: Discussionmentioning
confidence: 99%
“…Phenolics are well-studied for their correlation with Fusarium resistance in wheat (Engelharclt et al, 2002;Pani et al, 2014), maize (Atanasova-Penichon et al, 2012;Bakan et al, 2003) and barley (Bollina and Kushalappa, 2011).…”
Section: Accepted Manuscriptmentioning
confidence: 99%